1984
DOI: 10.1139/v84-130
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of Aconitumcolumbianum Nutt

Abstract: The most abundant readily isolated alkaloids of the aerial portion of Aconitumcolumbianum Nutt• were found to be talatisamine and cammaconine. New spectral data for known derivatives of these alkaloids and descriptions of new derivatives are presented. Less abundant alkaloids identified included the known ones sachaconitine, talatizidine, isotalatizidine, and 14-O-acetyltalatisamine, and the new ones 8-O-methyltalatisamine and a tetrahydroxymonomethoxy alkaloid, columbianine, with the same oxygenation pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 4 publications
5
35
0
Order By: Relevance
“…The structures of the known compounds were determined by comparison of spectroscopic data with those in the literature. Thus, seven known alkaloids were isolated for the first time from A. vilmorinianum, and these were identified to be N-deethyl-N-19-didehydrosachaconitine (5) [11], pengshenine B (6) [12], 8-O-methyltalatisamine (7) [9], 8-O-methylsachaconitine (8) [13], geniculatine C (9) [14], acoforesticine (10) [15], and austroconitine (11) [16]. The other seven alkaloids were determined to be talatisamine (12) [17], isotalatizidine (13) [18], vilmorrianine D (14) [4], vilmorrianine B (15) [4], vilmorrianine A (16) [3], yunaconitine (17) [19], and vilmorrianine C (18) [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of the known compounds were determined by comparison of spectroscopic data with those in the literature. Thus, seven known alkaloids were isolated for the first time from A. vilmorinianum, and these were identified to be N-deethyl-N-19-didehydrosachaconitine (5) [11], pengshenine B (6) [12], 8-O-methyltalatisamine (7) [9], 8-O-methylsachaconitine (8) [13], geniculatine C (9) [14], acoforesticine (10) [15], and austroconitine (11) [16]. The other seven alkaloids were determined to be talatisamine (12) [17], isotalatizidine (13) [18], vilmorrianine D (14) [4], vilmorrianine B (15) [4], vilmorrianine A (16) [3], yunaconitine (17) [19], and vilmorrianine C (18) [3].…”
Section: Resultsmentioning
confidence: 99%
“…Several alkaloids have been isolated from A. vilmorinianum before [3][4][5][6][7][8]. As part of our systematic investigations on the special herbal medicines used in clinical preparations in Yunnan Province, the chemical constituents of A. vilmorinianum were studied, and 18 norditerpenoid alkaloids were obtained, including three new compounds named vilmorrianines E-G (1-3) and a new natural product N-desethyl-N-formyl-8-O-methyltalatisamine (4), which was once reported as a synthetic product of the oxidation of 8-O-methyltalatisamine [9]. Among the 14 known compounds, there are seven alkaloids (5)(6)(7)(8)(9)(10)(11) isolated for the first time from this plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant absence of N-methyl, N-ethyl showed that there are no substitutions on the nitrogen atom of 3 besides the imine moiety (δ H 7.46 br s; δ C 169.9 d). The downfield signal at δ C 44.4 s can be assigned to C-4 adjacent to a double bond (N=C-19) [4]. Three methoxyl groups could be located at C-1, C-14, and C-16 based on the HMBC correlations of 1-OCH 3 (δ H 3.22) /C-1 (δ C 80.4), 14-OCH 3 (δ H 3.45)/C-14 (δ C 83.4), 16-OCH 3 (δ H 3.34)/C-16 (δ C 81.3) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of neutral materials with CHCl 3 (5×500 mL), the acidic solution was adjusted to pH 9.0 with 5% NaOH, and extracted with CHCl 3 (5×500 mL) to yield NDAs. 163 The two hydroxy groups in ANT-2, which were evident from the molecular mass and the carbon resonances at δ C 73.3 and 81.1, were located of necessity on C-10 and C-14.…”
Section: Isolation Of Alkaloids From a Anthoramentioning
confidence: 96%